The thin edge of the wedge: Extremely high extinction risk in wedgefishes and giant guitarfishes. Issue 7 (23rd April 2020) - Kyne, Peter M.; Jabado, Rima W.; Rigby, Cassandra L.; Dharmadi,; Gore, Mauvis A.; Pollock, Caroline M.; Herman, Katelyn B.; Cheok, Jessica; Ebert, David A.; Simpfendorfer, Colin A.; Dulvy, Nicholas K.
Abstract: The process of understanding the rapid global decline of sawfishes (Pristidae) has revealed great concern for their relatives, the wedgefishes (Rhinidae) and giant guitarfishes (Glaucostegidae), not least because all three families are targeted for their high‐value and internationally traded 'white' fins. The objective of this study was to assess the extinction risk of all 10 wedgefishes and six giant guitarfishes by applying the International Union for Conservation of Nature (IUCN) Red List Categories and Criteria, and to summarize the latest understanding of their biogeography and habitat, life history, exploitation, use and trade, and population status. Three of the 10 wedgefish species had not been assessed previously for the IUCN Red List. Wedgefishes and giant guitarfishes have overtaken sawfishes as the most imperilled marine fish families globally, with all but one of the 16 species facing an extremely high risk of extinction through a combination of traits: limited biological productivity; presence in shallow waters overlapping with some of the most intense and increasing coastal fisheries in the world; and overexploitation in target and by‐catch fisheries, driven by the need for animal protein and food security in coastal communities and the trade in meat and high‐value fins. Two species with very restricted ranges, the clown wedgefish ( Rhynchobatus cooki ) of the Malay Archipelago and the false shark ray ( Rhynchorhina mauritaniensis ) of Mauritania, may be very close to extinction. Only the eyebrow wedgefish ( Rhynchobatus palpebratus ) is not assessed as Critically Endangered, with it occurring primarily in Australia where fishing pressure is low and some management measures are in place. Australia represents a 'lifeboat' for the three wedgefish and one giant guitarfish species occurring there. To conserve populations and permit recovery, a suite of measures will be required that will need to include species protection, spatial management, by‐catch mitigation, and harvest and international trade management, all of which will be dependent on effective enforcement.